School Management Develop Students' Cognitive Ability Through The Tahfidz Program - Rizal Hidayat; Taqiyuddin Ibnu Syafii; Sukri Agustian; Mufthi Alam (Journal of Islamic Education and Ethics, 2023)
This study aims to understand how school management develops students' cognitive abilities through the Tahfidz program to determine how schools provide students with memorizing strategies. So they feel comfortable and not pressured into memorizing. This study uses field research by using a qualitative Exploration method. Data collection was carried out by focused observation, semi-structured interviews, and documentation, and lastly, data analysis was carried out. The results of this study are that the implementation of tahfidz activities is carried out based on the tahfidz class schedule in each class but is separated between junior high and high school. For junior high school classes, accompanied and directly controlled by ustadz Imam Hasanuddin. The memorization deposit will be listened to now by him for students who want to repeat murojaah before being deposited. High school students are more free to deposit memorization with anyone, both classmates and seniors, provided that the reciter has more memorization or has completed 30 juz of memorization.